IDENTIFIKASI TINGKAT KEBUGARAN JASMANI ANAK BERKEBUTUHAN KHUSUS TUNARUNGU SLB NEGERI MARLOSO KABUPATEN BURU - Kurniasih, Kurniasih; Latar, Idris Moh; Tahapary, Johni Melvin (STKIP Melawi, 2024)
Abstract: The aim of this research was to determine the level of physical fitness of Deaf Children with Special Needs at Marloso State Special School, Buru Regency. This research uses quantitative methods. The population in this study amounted to 65 students with special needs. From a population of 65 children with special needs at SLB Negeri Marloso and the sample used in the study the researcher used the porpusive sampling technique by taking samples for certain considerations, namely 11 deaf children out of 65 children with special needs. Samples were taken based on consideration, namely 11 students with special needs level 2 girls totaling 7 students and boys totaling 4 students. The data collection technique in this study used the Indonesian Student Fitness Test (TKSI) test norm. Based on the results of the above research, we can conclude that the level of physical fitness of children with special needs deaf SLB Negeri Marloso Buru Regency on average has a poor level of fitness. Keywords: Physical fitness, children with special needs, deafnessÂ Abstrak: Tujuan penelitian ini adalah untuk mengetahui tingkat kebugaran jasmani Anak Berkebutuhan Khusus Tunarungu SLB Negeri Marloso Kabupaten Buru. Penelitian ini menggunakan metode kuantitatif. Populasi pada penelitian ini berjumlah 65 siswa berkebutuhan khusus. Dari populasi 65 anak berkebutuhan khusus di SLB Negeri Marloso dan sampel yang digunakan dalam penelitian peneliti mengunakan teknik sampling porpusive dengan mengambil sampel atas pertimbangan tertentu yakni anak tunarunggu berjumlah 11 orang dari 65 anak berkebutuhan khusus. Sampel diambil berdasarkan pertimbangan yakni 11 siswa dengan kebutuhan khusus tuanrungu level 2 putri yang berjumlah 7 siswi dan putra berjumlah 4 siswa. Teknik pengumpulan data pada penelitian ini mengunakan norma tes Tes Kebugaran Siswa Indonesia (TKSI). Berdasarkan hasil penelitian diatas, maka dapat kita simpulkan bahwa tingkat kebugaran jasmani anak berkebutuhan khusus tunarungu SLB Negeri Marloso Kabupaten Buru rata â€“ rata memiliki tingkat kebugaran yang kurang baik.Kata Kunci: Kebugaran Jasmani, Anak Berkebutuhan Khusus, Tunarungu